Logistics and trade flows: Evidence from selected ECOWAS countries - Hassan O. Ozekhome; Hassan E. Oaikhenan (West African Journal of Monetary and Economic Integration, 2019)
The traditional trade literature has largely centered on the removal of artificial and non-artificial barriers to trade. The focus, has, however, in recent times, shifted to the role of logistics on trade flows, necessitating this study. Employing the Hausman-Taylor and system-GMM estimation techniques on a panel data from selected ECOWAS countries, the empirical results show that logistics has a positive but weak impact on trade in the sub-region. Foreign direct investment, world demand, exchange rate, the ease of doing business and socio-political indicator variable (which accounts for the stability of the social and political environment) are other critical variables that influence trade in the sub-region. The impact of financial development is positive but weak. We recommend amongst others, the building of sound logistics, increased investment in soft and hard infrastructure, improved ease of doing environment, and the harmonization and coordination of trade policies to enhance trade in the sub-region.
Keywords: 14; F15; E61; C13; 330; Logistics; Trade flows; ECOWAS; Hausman - Taylor; System-GMM